2015
DOI: 10.1080/00219266.2014.1000360
|View full text |Cite
|
Sign up to set email alerts
|

Mnemonics are an Effective Tool for Adult Beginners Learning Plant Identification

Abstract: Most beginners are introduced to plant diversity through identification keys, which develop differentiation skills but not species memorisation. We propose that mnemonics, memorable 'name clues' linking a species name with morphological characters, are a complementary learning tool for promoting species memorisation. In the first of two experiments, 64 adults in a group-learning environment were taught species identification using mnemonics, an educational card game and a text-based dichotomous key. In the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Stagg, Donkin, and Smith 2014;Stagg and Donkin 2015), including the number of focal species, length and format of research trials.…”
Section: Methodsmentioning
confidence: 99%
“…Stagg, Donkin, and Smith 2014;Stagg and Donkin 2015), including the number of focal species, length and format of research trials.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the interviewees mentioned creative forms to translate biodiversity to a broad audience, such as metaphors, mnemonics and games, which according to past studies add to people's learning process. For instance, it has been demonstrated that good mnemonics linking the name of a species to its morphology produce higher retention rates than pictorial determination keys, making them an effective teaching method in education alongside field work [137].…”
Section: Best Practices In Communicating Biodiversity Amongst Dutch Bmentioning
confidence: 99%
“…Mnemonic cues may be especially helpful to re-code information in domains where learners must master a wealth of unfamiliar vocabulary or abstract concepts. Indeed, students report generating mnemonic cues for classes that specifically involve learning a lot of new facts and terminology (McCabe, Osha, Roche, & Susser, 2013), and relying on memory cues has advantages for complex domains with vast new vocabularies, including chemistry (Banks, 1941), physics (Gough, 1977), biology (Stagg & Donkin, 2016), and psychology (Richmond, Carney, & Levin, 2011).…”
Section: Kinds Of Self-generated Cuesmentioning
confidence: 99%